Shields textbook of glaucoma - Allingham, R. Rand; Allingham, R. Rand.; Damji, Karim F.; Shields, M. Bruce (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Thoroughly updated, and now in full color, Shields' Textbook of Glaucoma, Sixth Edition is a clinically focused and practical textbook for general ophthalmologists treating patients with glaucoma. This classic text offers a rational approach to the medical and surgical management of glaucoma and presents a total care plan for the patient. This edition has five new or reconfigured chapters--management of the glaucoma patient/approach to the patient; principles of medical therapy; adrenergic agonists and antagonists; cholinergic stimulators and hyperosmotic agents; and neuroprotection and other investigational drugs. The book examines new technologies for intraocular pressure assessment and current diagnostic technologies such as optical coherence tomography, spectral domain optical coherence tomography, Heidelberg retinal tomograph, and GDx. Noted experts detail advances in surgical treatment of glaucoma including new glaucoma implants and angle surgery. Coverage also includes advances in genetics of glaucomatous diseases. A companion website includes the fully searchable text and an image bank"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Glaucoma; Glaucoma